Early versus delayed removal of indwelling urinary catheter after elective cesarean delivery: systematic review and meta-analysis of randomized controlled trials. (17th August 2020) - Menshawy, Amr; Ghanem, Esraa; Menshawy, Esraa; Masoud, Ahmed Taher; El-Sharkawy, Mohamed; Taher, Ayman; Mahmoud, Mostafa; Khamis, Yasser; Haggag, Hisham; Khalifa, Mansour; Samy, Ahmed; Abbas, Ahmed M.
Abstract: Background: Timing of removal of the indwelling urinary catheter after elective cesarean delivery (CD) is controversial. Early removal could be associated with fewer urinary symptoms. Objective: This review aims to evaluate the evidence from published randomized clinical trials (RCTs) about the outcomes of early versus delayed removal of indwelling urinary catheter after elective cesarean delivery (CD). Data sources: Electronic databases were searched using the following MeSH terms (early Or Late Or immediate OR delayed removal) AND (Urinary catheter) AND (cesarean section OR cesarean delivery OR CS) Methods of study selection: All RCTs assessing the timing of removal of urinary catheter were considered for this meta-analysis. One hundred seventy-two studies were identified of which three studies deemed eligible for this review. Quality and risk of bias assessment were performed for all studies. Data extraction: Two researchers independently extracted the data from the individual articles and entered into RevMan software. The relative risk (RR), the weighted mean difference (WMD) and 95% confidence interval (CI) were calculated. The extracted outcomes were significant bacteriuria, urinary symptoms (urinary retention necessitating re-catheterization, dysuria, urinary frequency, urgency) postoperative oral rehydration and length of hospital stay. Results: Three RCTs (early removal: n  = 298 and delayed removal: n  = 311) were included. The pooled estimate showed that early removal significantly reduced dysuria (RR = 0.60, 95% CI [0.38, 0.95], p =.03), urinary frequency (RR = 0.32, 95% CI [0.16, 0.66], p =.002) and significant bacteriuria (RR = 0.49, 95% CI [0.30, 0.83], p =.007) than delayed removal. Conclusions: This meta-analysis suggests that early removal of the indwelling urinary catheter in patients who underwent elective CD showed significant less dysuria, less urinary frequency and a decrease in the incidence of significant bacteriuria.